Kinetic spectrophotometric method for determination of amlodipine besylate in its pharmaceutical tablets - Ashraf M. Mahmoud; Hanaa M. Abdel-Wadood; Niveen A. Mohamed (Elsevier, 2012)
A simple and sensitive kinetic spectrophotometric method has been developed and validated for determination of amlodipine besylate (AML). The method was based on the condensation reaction of AML with 7-chloro-4-nitro-2,1,3-benzoxadiazole in an alkaline buffer (pH 8.6) producing a highly colored product. The color development was monitored spectrophometrically at the maximum absorption Î»max 470Â nm. The factors affecting the reaction were studied and the conditions were optimized. The stoichiometry of the reaction was determined, and the reaction pathway was postulated. Moreover, both the activation energy and the specific rate constant (at 70Â Â°C) of the reaction were found to be 6.74Â kcalÂ moleâ1 and 3.58Â sâ1, respectively. The initial rate and fixed time methods were utilized for constructing the calibration graphs for the determination of AML concentration. Under the optimum reaction conditions, the limits of detection and quantification were 0.35 and 1.05Â Î¼g/mL, respectively. The precision of the method was satisfactory; the relative standard deviations were 0.85â1.76%. The proposed method was successfully applied to the analysis of AML in its pure form and tablets with good accuracy; the recovery percentages ranged from 99.55Â±1.69% to 100.65Â±1.48%. The results were compared with that of the reported method. Keywords: Amlodepine besylate, 7-chloro-4-nitro-2,1,3-benzoxadiazole, Kinetic analysis, Spectrophotometry